Interactions between the intestinal microbiome and helminth parasites - Zaiss, M. M. (Parasite Immunol, 2015)
Throughout evolution, both helminths and bacteria have inhabited our intestines. As intestinal helminths and bacteria inhabit the same environmental niche, it is likely that these organisms interact with, and impact on, each other. In addition, intestinal helminths are well known to alter intestinal physiology, permeability, mucous secretion and the production of antimicrobial peptides – all of which may impact on bacterial survival and spatial organization. Yet despite rapid advances in our understanding of host–intestinal bacteria interactions, the impact of helminths on this relationship has remained largely unexplored. Moreover, although intestinal helminths are generally accepted to possess potent immuno‐modulatory activity, it is unknown whether this capacity requires interactions with intestinal bacteria. We propose that this ‘ménage à trois’ situation is likely to have exerted a strong selective pressure on the development of our metabolic and immune systems. Whilst such pressures remain in developing countries, the eradication of helminths in industrialized countries has shifted this evolutionary balance, possibly underlying the increased development of chronic inflammatory diseases. Thus, helminth–bacteria interactions may represent a key determinant of healthy homoeostasis.